Vacant Land Plots in Afghan Cities: A Problem and an Opportunity. (November 2016) - French, Matthew; Turkstra, Jan; Farid, Mohammad
Vacant land plots in and around the cities of Afghanistan are a major phenomenon. They are defined as subdivided but unoccupied parcels of land. Due to their scale and dubious ownership, they pose a major problem for effective land management and administration, urban governance and urban planning. This article examines the quantitative scale of the vacant plots in the 34 provincial capitals based on data interpreted from recent high-resolution satellite imagery. It shows that, on an average, 27 per cent of the built-up area of Afghan cities consists of vacant plots conforming to two broad typologies based on location: small-scale inner city plots and plots in large-scale land subdivisions and townships on the urban periphery. The article goes on to examine how these plots have come to be and remained vacant, as a result of incremental occupation by households; land sales by municipalities; and land-grabbing/usurpation, especially by the elite, warlords and informal power brokers, often in collusion with state actors—all buoyed by a decade of strong economic growth and the rise of a highly speculative urban real estate market. The article concludes by presenting key policy and programme options to address this phenomenon in order to improve urban land administration, redress injustices, generate revenues from land taxes, increase access to land and promote urban inclusion.